Studying Poetry through Music: The Tasso in Music Project - Emiliano Ricciardi; Craig Stuart Sapp (Journal of the Text Encoding Initiative, 2025)
The Tasso in Music Project (https://​tassomusic.​org) is a digital critical edition of the early modern musical settings of the poetry of Torquato Tasso (1544–95). Comprising about eight hundred musical settings and representing the work of over two hundred composers, this repertoire is significant not only for musical reasons, but also for literary reasons, since these musical settings shed light on the dissemination of Tasso’s work and offer insight into the form and meaning of his poems. Accordingly, besides providing newly made critical editions of the musical settings in a variety of electronic formats (Humdrum, MEI, MusicXML), the project features a wide array of tools designed to illuminate the tradition of the poetic texts and music/text relations. More specifically, the project includes TEI transcriptions of the poetic texts as they appear in musical settings and in contemporaneous literary sources, both manuscript and printed, with dynamic visualization of literary variants across sources. This dynamic collation of variants provides indispensable data for the study of the notoriously intricate transmission of Tasso’s poetry. Likewise, the Tasso in Music Project features newly developed tools for the study of music-text relations, such as computational analysis of poetic prosody/musical rhythm and musical cadences/poetic syntax, which show how a musical setting can function as a parsing of a poem’s metrical/syntactic structure. Through its editions and tools, the Tasso in Music Project addresses a wide audience encompassing not only music scholars and performers, but also literary scholars. At the same time, the project provides a digital framework in which music and poetry receive equal attention, as do philology and analysis.